Peta konsep Pendidikan Islam Perspektif Imam Ghazali - Celsey Olivianti Putri; Zeda Imania; Rodia Indah; Moh Faizin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article thoroughly examines Imam Al-Ghazali's views on Islamic education and adab, with an emphasis on a holistic framework that combines knowledge, faith, charity, and morals to form an insān kāmil (perfect human being). Al-Ghazali, a scholar from Tus, Persia, in the 11th century, defined education as a process of moral development and purification of the soul. The main goal of education is to obtain worldly and spiritual happiness. He opposes the educational paradigm of modern philosophers which focuses only on rationality. He emphasized that knowledge without adab is like fire which has no light.Adab is the main pillar of the educational process and helps children learn noble qualities such as patience, humility and honesty. This is implemented from an early age through spiritual practices such as dhikr and muhasabah. In his great works, such as Iḥyā' 'Ulūm ad-Dīn, Ayyuhal Walad, and Tahāfut al-Falāsifah, Al-Ghazali combines rationalism with Sufism. He opposed the dichotomy between worldly knowledge (such as medicine and mathematics) and the hereafter, claiming that revelation provides a balance to prevent misguidance. His educational methods, based on internalizing values, examples, and ethical discussions, support the role of teachers as moral and spiritual role models and students as ethical learners. This thinking is highly relevant to modern education, especially in Indonesia, where a character-based curriculum is implemented by the Ministry of Education and Culture and institutions such as the State Islamic University (UIN) use a holistic approach to address the moral crisis caused by technological advancements. The main challenge lies with educators who lack an understanding of Sufism, which requires intensive training.